2010
DOI: 10.1016/j.jaci.2009.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for neuronal expression of functional Fc (ε and γ) receptors

Abstract: The Fc receptor family plays a key role in adaptive immunity through the binding of immunoglobulin antibodies that recognize an immune insult and elicit an inflammatory response leading to its clearance. Dysregulation of this receptor family may have untoward consequences that result in autoimmune and allergic diseases. Many of these diseases seem to involve the nervous system and are exacerbated by stress or other neurological challenges. Recently, the presence of Fc receptors was uncovered on dorsal root gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 9 publications
3
55
0
Order By: Relevance
“…Recent studies revealed the presence of FcγRI on both DRG (Andoh and Kuraishi, 2004) and superior cervical ganglion neurons of mice (van der Kleij et al, 2010). The present study showed that FcγRI, but not FcγRII or FcγRIII, is expressed on a subpopulation of rat DRG neurons, consistent with previous reports (Andoh and Kuraishi, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the presence of FcγRI on both DRG (Andoh and Kuraishi, 2004) and superior cervical ganglion neurons of mice (van der Kleij et al, 2010). The present study showed that FcγRI, but not FcγRII or FcγRIII, is expressed on a subpopulation of rat DRG neurons, consistent with previous reports (Andoh and Kuraishi, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that in the absence of brain-resident CD8 + T cells, unrestricted CD4 + T cell activity and IgE production could be responsible for disease aggravation in lupus-prone mice. Interestingly, the high affinity IgE receptor, FcεRI, was recently shown to be expressed on neurons59, which indicates that any IgE entering the brain has the potential to induce a local inflammatory response. While it is clear that CD8 + T cells are required to regulate the antibody response in TLR7[Tg] lupus-prone mice, more studies will need to be performed to fully elucidate any regulatory mechanism that may be imparted by these brain-resident CD8 + T cells and determine if they are similar in function to memory cells previously described in models of viral or bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility, also barrowing from observations from studies targeting Aβ, is that unbound antibody can enter neurons: targeting tau directly within the cells. Neurons have been shown to possess receptors that can bind and internalize IgG [27], and thus, could actively internalized antibodies to tau, which would then subsequently target intraneuronal pools of aggregated tau. Once the antibody-tau complex is formed, it has been hypothesized that a final destination is likely the endosomal/lysosomal system for degradation [22].…”
Section: Discussionmentioning
confidence: 99%